Peptic digestion of beef myofibrils is modified by prior marination - Nash Patel (Food & Nutrition Research, 2013)
Background: Preparatory steps such as seasoning, marination, and cooking may induce changes in meat which affects the ability of the stomach to adequately digest it. This may result in peptide chains reaching the colon intact where resident bacteria ferment them resulting in the formation of putative carcinogenic phenolic by-products. Objective: In this study, we set out to determine whether peptic digestion of beef myofibrils was influenced by prior marination. Design: Cubes of sirloin stewing steak were marinated in balsamic vinegar or left untreated at 4°C overnight. Samples were oven cooked and myofibrils were extracted. Myofibrils were subject to proteolytic digestion with pepsin and digestion products analysed spectrophotometrically and with gel electrophoresis. Results: Both marination in balsamic vinegar and cooking significantly reduced the yield of myofibrils from shop-purchased beef (P<0.05). Digestion progressed in all samples as a function of time (P<0.01), varying depending on prior treatment. Marination induced resistance to the digestive effect of pepsin during the early to mid-phase of digestion, and we identified a protein band of ∼150 kDa which was protected from peptic digestion in samples which had been marinated and cooked, but not in any other groups. Conclusions: Pre-treatment of meat prior to cooking may influence specific peptides such that they become more resistant to the digestive actions of pepsin.